THE IMPROVEMENT OF ENGLISH SPEAKING SKILLS IN XI CLASS IPS 3 STUDENTS USING ROLE PLAYING METHOD - Dina Rizkia Fitrillah; Hidayatur Rohmah; Yuyun Bahtiar (Universitas KH. A. Wahab Hasbullah, 2019)
ABSTRACT This study aims to determine the application of Role-Playing Method (Role Play) that increases in improving students' ability to speak English or not XI Class IPS 3 MA Negeri 10 Jombang. Researcher used Role Play Method to improve students' speaking abilities. Researcher uses the descriptive qualitative research. The research subjects were students of class XI. Researcher took a class used in research consisting of 22 students. After using the Role Play Method, the students are able to improve their speaking ability. This improvement was demonstrated through observation, interviews and tests. Keywords: Speaking Ability, Role Play Techniques ABSTRAK Penelitian ini bertujuan untuk mengetahui penerapan metode bermain peran (Role Play) itu meningkat dalam meningkatkan kemampuan siswa dalam berbicara Bahasa Inggris atau tidak di kelas XI MA Negeri 10 Jombang. peneliti menggunakan metode Role Play untuk meningkatkan kemampuan berbicara siswa. Penulis menggunakan penelitian Deskriptif kualitatif. Subjek penelitian adalah siswa kelas XI. Penulis mengambil satu kelas di gunakan dalam penelitianterdiri dari 22 siswa. Setelah menggunakan metode Role Play, siswa mampu meningkatkan kemampuan berbicaranya. Peningkatan ini ditunjukkan melalui Observasi, wawancara serta test. Kata Kunci: Kemampuan Berbicara, Teknik Role Play